Operationalizing Humility: A Model of Situational Humility for Christian College Student Leaders. Issue 4 (2nd October 2018) - Barrett, Scott
Abstract: This research study explored how college student leaders operationalize humility in their actions and what leads individuals to act with situational humility. Using a grounded theory approach, the researcher examined the process of humility development. Based on the data collected, three main themes emerged: Faith and humility go hand in hand, a sense of self impacts humbling experiences, and the humility affects relationships in specific ways. For these students, humbling experiences occurred when their sense of self did not line of up with their experience of the world. Individuals then moved to the point of change where they decided whether to reorient their sense of self or actions or not reorient and act with pride. Individuals were positively impacted towards humility by their Christian belief system, empathy, being in relationship, and interacting with others who were different from them. The implications of this research for institutional leaders include valuing how humility is seen as a virtue, helping to develop empathy in students, and providing opportunities for students to be in relationship with others, specifically those who are different from themselves.